Trend in active transportation to school among Swiss school children and its associated factors: three cross-sectional surveys 1994, 2000 and 2005 - Bringolf-Isler Bettina; Grize Leticia; Martin Eva; Braun-Fahrländer Charlotte (BMC, 2010)
Abstract Background Giving the rising trend in childhood obesity in many countries including Switzerland, strategies to increase physical activity such as promoting active school travel are important. Yet, little is known about time trends of active commuting in Swiss schoolchildren and factors associated with changes in walking and biking to school. Methods Between 1994 and 2005, information about mobility behaviour of children aged 6-14 years was collected within three Swiss population based national travel behaviour surveys. Mode of transport to school was reported for 4244 children. Weighted multivariate logistic regression analyses were used to assess active school travel time trends and their influencing factors. Results More than 70% of Swiss children walked or biked to school. Nevertheless, the proportion of children biking to school decreased (p = 0.05, linear trend), predominately in urban areas, and motorized transportation increased since 1994 (p = 0.02). Distance to school did not change significantly over time but availability of bikes decreased (p < 0.001) and number of cars per household increased (p < 0.001). The association between survey year and bike use was significantly modified by living in an urban area (OR (95%CI): 1.0, 0.63 (0.44-0.90), 0.71 (0.49-1.03), respectively for 1994, 2000 and 2005) and by distance to school (OR (95%CI): 1.0, 0.65 (0.40-1.05), 0.50 (0.23-0.79) for the same years and for children who lived more than a mile away from school). Conclusions Programs to encourage safe biking and to limit car use as mode of transport to school are warranted to stop this trend.